-8(2b+1)+(17b-2)=0

Simple and best practice solution for -8(2b+1)+(17b-2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(2b+1)+(17b-2)=0 equation:


Simplifying
-8(2b + 1) + (17b + -2) = 0

Reorder the terms:
-8(1 + 2b) + (17b + -2) = 0
(1 * -8 + 2b * -8) + (17b + -2) = 0
(-8 + -16b) + (17b + -2) = 0

Reorder the terms:
-8 + -16b + (-2 + 17b) = 0

Remove parenthesis around (-2 + 17b)
-8 + -16b + -2 + 17b = 0

Reorder the terms:
-8 + -2 + -16b + 17b = 0

Combine like terms: -8 + -2 = -10
-10 + -16b + 17b = 0

Combine like terms: -16b + 17b = 1b
-10 + 1b = 0

Solving
-10 + 1b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + 1b = 0 + 10

Combine like terms: -10 + 10 = 0
0 + 1b = 0 + 10
1b = 0 + 10

Combine like terms: 0 + 10 = 10
1b = 10

Divide each side by '1'.
b = 10

Simplifying
b = 10

See similar equations:

| 320(t)=-16t^2+190t+20 | | 3+12a+3*4a-2+4b+7b*4/2 | | -4(5-y)=20 | | 14(5-y)=20 | | x^2(5x-1/4)(2x+1/4) | | 1.7q-1.6-5.9q=5.2q-4.1 | | -3(2x-6)-4x+9= | | 7y+1=8y+5 | | x^2-x+64=0 | | 6x^2+12x+c=0 | | 8x+17=5x+35 | | x^2+4x+48=0 | | 8/x-5x=4 | | 5x^2-78=48 | | a=10ln(a) | | x-1-(x-2)(x+2)=9 | | 7.5m+1.1-10m=4.3-2.5m-3.2+1.7 | | 2x-8x+29=5 | | -3(-2)+y=-5 | | 6y/z | | -39-20+y=-5 | | -13-4x=-21 | | 2*(x+3)=a | | -20x^2+12x+27=0 | | 2x(x+3)=a | | 0=6x^2+6 | | 5(x-1)-2(x^2+5x+6)-7(x+6)= | | x+3/10=-3/10 | | 6x(x-2)=11 | | -6+4x=34 | | -7b+4=39 | | 7-4m=51 |

Equations solver categories